2018
DOI: 10.1186/s13007-018-0308-5
|View full text |Cite
|
Sign up to set email alerts
|

Land-based crop phenotyping by image analysis: consistent canopy characterization from inconsistent field illumination

Abstract: BackgroundOne of the main challenges associated with image-based field phenotyping is the variability of illumination. During a single day’s imaging session, or between different sessions on different days, the sun moves in and out of cloud cover and has varying intensity. How is one to know from consecutive images alone if a plant has become darker over time, or if the weather conditions have simply changed from clear to overcast? This is a significant problem to address as colour is an important phenotypic t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 42 publications
0
20
0
Order By: Relevance
“…The calibration target was attached to the base of the platform such that it was always visible from the perspective of one camera as described in Appendix C. Colour calibration was performed on all images according to the method proposed in [41]. Field imaging was carried out between 23 September 2016 and 18 November 2016 inclusive (see Table 2).…”
Section: Image Data Collection and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The calibration target was attached to the base of the platform such that it was always visible from the perspective of one camera as described in Appendix C. Colour calibration was performed on all images according to the method proposed in [41]. Field imaging was carried out between 23 September 2016 and 18 November 2016 inclusive (see Table 2).…”
Section: Image Data Collection and Analysismentioning
confidence: 99%
“…On the other hand, remote images of the field are captured with sensors attached to aerial platforms [36][37][38][39] for trait estimation. Recent studies to quantify plant canopy development from images either report trait comparisons with reference to a different sensor technology such as LiDAR [16,40] or compare image-based estimation techniques with manual methods [5,41]. A comparison of the performance of two imaging methods on the same field study has hitherto not been reported previously.…”
Section: Introductionmentioning
confidence: 99%
“…It was also noted that the color corrected images had consistently higher 385 green intensity than red and blue due to the high chlorophyll content at the seedling stage. While at 386 the senescence stage, the red value is expected to be increased, as plants begin to turn yellow with 387 decreased chlorophyll content (data was not shown here) [55]. It would be very difficult to observe Our study focused on improving the efficiency of the color calibration process using a deep learning-based method and demonstrating its applicability in real-time series data and did not consider its implications and usefulness for typical plant phenotyping analyses since this was demonstrated in several studies [55,56].…”
mentioning
confidence: 81%
“…While at 386 the senescence stage, the red value is expected to be increased, as plants begin to turn yellow with 387 decreased chlorophyll content (data was not shown here) [55]. It would be very difficult to observe Our study focused on improving the efficiency of the color calibration process using a deep learning-based method and demonstrating its applicability in real-time series data and did not consider its implications and usefulness for typical plant phenotyping analyses since this was demonstrated in several studies [55,56]. For example, color-corrected images are useful for detecting the variations among different plant varieties or plants grown under different nitrogen concentrations, and even plants grown under inconsistent illumination conditions [57].…”
mentioning
confidence: 81%
See 1 more Smart Citation